Treatment of prolactinomas with megavoltage radiotherapy. - Grossman, A; Cohen, B; Charlesworth, M; Plowman, P; Rees, L; Wass, J; Jones, A; Besser, G (1984)
The outcome of treatment of 36 women with prolactinomas using megavoltage radiotherapy combined with interim dopamine agonists (bromocriptine, lysuride, pergolide) was reviewed; 16 of the women showed radiological evidence of a macroadenoma. The most common presenting symptom was secondary amenorrhoea; 26 of the patients had galactorrhoea. In 29 patients who wished to conceive the ovulation rate (as indicated by circulating progesterone concentrations) was 97% and the successful fertility rate 86%. No patient had enlargement of the tumour during pregnancy and there were no complications of radiotherapy. No further tumour enlargement was detected in serial skull radiographs, and an improvement in size of the fossa was noted in 45% of those assessed. When medical treatment was withdrawn a mean of 4.2 years (range 1-11) after radiotherapy in the 27 patients who had completed their families the serum prolactin concentration had fallen appreciably in 26 of them and later became normal in eight. The incidence of growth hormone deficiency rose from 24% of the whole group before radiotherapy to 79% afterwards. Only one patient required thyroxine, and one was receiving gonadotrophin. No patient became deficient in adrenocorticotrophic hormone. A regimen of megavoltage radiotherapy and interim bromocriptine allows women with prolactinomas safely to undergo pregnancy and results in the long term prospect of tumour shrinkage and control of hyperprolactinaemia.